Health care costs and service utilization in the first year following moderate to severe traumatic injury - Mari Storli Rasmussen; Yuan Zhang; Nada Andelic; Eline Aas (BMC Health Services Research)
Abstract Background Most of the previous studies on costs following trauma have focused solely on in-hospital costs and costs associated with the acute treatment and early rehabilitation. As a result, post-hospital costs are often neglected in the estimation of total costs. We aimed to describe service utilization and total costs for health care services, rehabilitation services, and social support in the periods 0–6 months and 7–12 months after moderate-to-severe traumatic injury. Further, we explored costs and their associations with sociodemographic, clinical and injury-related variables. Methods Data were obtained from a prospective, 12 months follow-up study of patients in all ages with moderate-to-severe traumatic injury determined by a New Injury Severity Score (NISS) > 9, admitted directly or within 72 h to the trauma referral centres in year 2020. Data on utilization of health care and rehabilitation services from the Norwegian Patient Register (NPR), the Municipal patient and user register (KPR), and the Norwegian Control and Payment of Health Reimbursements Database (KUHR) were used. Results A total of 601 patients were included, 24% with moderate and 76% with severe injuries. The overall mean total health care cost per patient in the first year after traumatic injury was 846,877 (SD 1,042,649) Norwegian Kroner (NOK). The mean total cost of rehabilitation per patient was 251,487 (SD 317,050) NOK. Most costs were attributable to secondary care in the first six months post-injury. Severely injured patients had a higher health care utilization and average cost compared to those with moderate injury. Injury severity factors were the most prominent cost drivers, and number of injuries, severe head, spine, and extremity injuries were significantly associated with higher costs during the first year following trauma. Conclusions The findings give a holistic insight into health care utilization and costs for patients across all ages with complex needs following trauma and can contribute to the planning and provision of services for this patient group.